2021
DOI: 10.1111/wrr.12916
|View full text |Cite
|
Sign up to set email alerts
|

To compare the effect of sea buckthorn and silver sulfadiazine dressing on period of wound healing in patients with second‐degree burns: A randomized triple‐blind clinical trial

Abstract: Burn injuries can be associated with the incidence of disability and death, yet their management remains a costly difficult problem. We conducted this clinical trial to evaluate the period of wound healing with sea buckthorn dressings for the seconddegree burns and compare the results with 1% silver sulfadiazine (SSD) dressings. This randomized triple-blind clinical trial was conducted in a hospital in Isfahan, Iran.Fifty-five patients suffering second-degree burns were recruited through convenient sampling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In a randomised, triple-blind clinical trial, the effectiveness of sea buckthorn cream and 1% SSD cream in treating burns was investigated and compared [ 28 ]. The study involved 30 patients with second-degree thermal burns that affected no more than 10% of their total body surface area and occurred within 6 hours of arrival at the hospital.…”
Section: Resultsmentioning
confidence: 99%
“…In a randomised, triple-blind clinical trial, the effectiveness of sea buckthorn cream and 1% SSD cream in treating burns was investigated and compared [ 28 ]. The study involved 30 patients with second-degree thermal burns that affected no more than 10% of their total body surface area and occurred within 6 hours of arrival at the hospital.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a randomized triple-blind clinical trial demonstrated that the healing period for second-degree burns in patients treated with 40% sea buckthorn cream was about 5 days shorter than for patients treated with 1% silver sulfadiazine dressings. The sea buckthorn cream had better clinical efficacy and shortened the healing time for second-degree burns ( 74 ). It was found that sea buckthorn seed oil promoted wound contraction by increasing hydroxyproline, hexosamine, DNA, and total protein content, which in turn promoted full-layer burn wound healing.…”
Section: Health Benefitsmentioning
confidence: 99%
“…Sea buckthorn (especially the oils) is well known for its wound and burn-healing properties. Abdullahzadeh and Shafiee ( 2021 ) compared the effectiveness of a cream containing 40% of “the active ingredient of sea buckthorn” fruit in treatment of second-degree burns, with that of a 1% silver sulfadiazine (SSD, a topical medicine commonly used for treatment of burns) cream. A randomized triple-blind clinical trial comprised 55 hospital patients.…”
Section: Pharmacologymentioning
confidence: 99%